2019
DOI: 10.1177/1352458519881761
|View full text |Cite
|
Sign up to set email alerts
|

Diroximel fumarate (DRF) in patients with relapsing–remitting multiple sclerosis: Interim safety and efficacy results from the phase 3 EVOLVE-MS-1 study

Abstract: Background: Diroximel fumarate (DRF) is a novel oral fumarate for patients with relapsing–remitting multiple sclerosis (RRMS). DRF and the approved drug dimethyl fumarate yield bioequivalent exposure to the active metabolite monomethyl fumarate; thus, efficacy/safety profiles are expected to be similar. However, DRF’s distinct chemical structure may result in a differentiated gastrointestinal (GI) tolerability profile. Objective: To report interim safety/efficacy findings from patients in the ongoing EVOLVE-MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 19 publications
8
59
1
Order By: Relevance
“…Interestingly, the rates of investigator-assessed GI AEs and discontinuations because of GI AEs reported for DRFand DMF-treated patients were consistent with rates in the ongoing EVOLVE-MS-1 study, as well as with rates in the pivotal DEFINE and CONFIRM studies, though the trials cannot be directly compared [4,5,14]. The incidence of flushing, though numerically lower with DRF than DMF in this study, was generally consistent with rates reported in phase III studies with DRF and DMF [4,5,14]. However, as the focus of EVOLVE-MS-2 was GI tolerability, we did not evaluate and cannot assess the impact of flushing on patients in the study.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Interestingly, the rates of investigator-assessed GI AEs and discontinuations because of GI AEs reported for DRFand DMF-treated patients were consistent with rates in the ongoing EVOLVE-MS-1 study, as well as with rates in the pivotal DEFINE and CONFIRM studies, though the trials cannot be directly compared [4,5,14]. The incidence of flushing, though numerically lower with DRF than DMF in this study, was generally consistent with rates reported in phase III studies with DRF and DMF [4,5,14]. However, as the focus of EVOLVE-MS-2 was GI tolerability, we did not evaluate and cannot assess the impact of flushing on patients in the study.…”
Section: Discussionsupporting
confidence: 55%
“…The distinct chemical structure of DRF is hypothesized to elicit less irritation in the GI tract than DMF through lower production of methanol (a GI-irritating promoiety), and less reactivity with pre-systemic off-target proteins or receptors [13]. Interim findings from the ongoing, multicenter, 2-year, prospective, single-arm, open-label DRF phase III EVOLVE-MS-1 study have demonstrated a low rate (~ 31%) of GI AEs when considered within the context of those reported in separate clinical trials and real-world effectiveness studies of DMF [9,10,14]. Notably, < 1% of patients in the EVOLVE-MS-1 study discontinued DRF treatment because of GI AEs [14].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Alkermes, Inc. has developed diroximel fumarate (DRF), also known as ALKS8700, a novel MMF prodrug. Importantly, this new formulation has been shown to yield bioequivalent levels of MMF at the cellular level when compared directly to DMF (Figure 1) [108] while interacting less with off-target proteins and therefore producing fewer unwanted side effects [109]. Indeed, interim findings from EVOLVE-MS-1 and EVOLVE-MS-2 which demonstrate that DRF has a favorable safety and efficacy profile and is well-tolerated in MS patients [108,110].…”
Section: Safety Profilementioning
confidence: 99%